2018
DOI: 10.1083/jcb.201801044
|View full text |Cite
|
Sign up to set email alerts
|

Basal mitophagy is widespread in Drosophila but minimally affected by loss of Pink1 or parkin

Abstract: PINK1/parkin are key mediators of stress-induced mitophagy in vitro, but their impact on basal mitophagy in vivo is unclear. Novel Drosophila reporter lines reveal abundant mitophagy in many tissues, including dopaminergic neurons, that is unaffected by loss of PINK1/parkin.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
277
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 290 publications
(302 citation statements)
references
References 37 publications
23
277
2
Order By: Relevance
“…We wondered whether, by analogy with the role of USP30 in Parkin-overexpressing cells, this increase in mitophagy was dependent on PINK1. Depleting PINK1 did not affect basal levels of mitophagy, in agreement with two recent reports in mitophagy reporter flies and mice [19,20]. However, PINK1 depletion did suppress the enhancement of mitophagy seen upon USP30 knockdown ( Fig 1D).…”
Section: Enhancement Of Basal Mitophagy By Usp30 Depletion Is Dependesupporting
confidence: 92%
“…We wondered whether, by analogy with the role of USP30 in Parkin-overexpressing cells, this increase in mitophagy was dependent on PINK1. Depleting PINK1 did not affect basal levels of mitophagy, in agreement with two recent reports in mitophagy reporter flies and mice [19,20]. However, PINK1 depletion did suppress the enhancement of mitophagy seen upon USP30 knockdown ( Fig 1D).…”
Section: Enhancement Of Basal Mitophagy By Usp30 Depletion Is Dependesupporting
confidence: 92%
“…However, evidence for the role of the PINK1-Parkin pathway in mitophagy in vivo is limited. Recent studies in mouse and Drosophila showed that basal mitophagy in vivo is PINK1-Parkin pathway independent (37,38). Consistent with these results, we did not observe significant differences in the levels of basal mitophagy in the wing discs of L3 larvae and in dopaminergic neurons of adults after knock down of PINK1 or parkin (unpublished data).…”
Section: Changes In the Mitophagy Level During Drosophila Developmentsupporting
confidence: 91%
“…The role of the PINK1-Parkin pathway in the removal of damaged mitochondria has been well demonstrated in human cell systems (5), but evidence for the role of PINK1 and parkin in mitophagy in vivo is very limited. Several recent studies have shown that loss of PINK1 has no significant effect on mitophagy levels in different tissues (37,38), suggesting that PINK1 function is dispensable for basal mitophagy (45,46). Recently, PINK1 2/2 mice have been shown to be defective in the induction of mitophagy upon exhaustive exercise (14).…”
Section: Discussionmentioning
confidence: 99%
“…Although basal mitophagy has been recently demonstrated to occur in neurons in vivo both in Drosophila and mouse (Cornelissen et al, 2018;Lee et al, 2018;McWilliams et al, 2018), evidence for neuronal mitophagy specifically in response to acute mitochondrial stress remains sparse (Cummins & Götz, 2017;Whitworth & Pallanck, 2017). Consequently, we used C. elegans to test the effect of tau on mitophagy in a live nervous system.…”
Section: Discussionmentioning
confidence: 99%